Eksplorasi material daur ulang kantong plastik dengan teknik origami - Devanny Gumulya (Institut Seni Indonesia Yogyakarta, 2021)
Shopping plastic bag is a thermoplastic type LDPE and HDPE, that can be heated with hotpress. Through this recycling process come new material that can used for product material. The recycle plastic material has a lot of potential to be used as a product application. market research From founded many brands that try to recycle plastic still using another new material to give support to the plastic recycle material. Origami is a paper folding art that is commonly known by everyone. The study tried to apply the origami technique on recycled plastic bag material that has been heated with hotpress machine. With origami technique 90% the product can be made with this material entirely without the help of sewing and other materials. This is seen as an opportunity for the market that still use many new materials to support this material. The folding gives construction to the one sheet material and give new function to the recycle plastic material. The research uses experimental method. Series of paper origami patterns are applied on the recycle material, till founded several folding that can be apply on the recycle plastic sheet material. The research result is a variety of functional products made with origami techniques that have been egistered design industry copy wright.